Obstacles to dialogic encounters between parents and staff in pre-primary school - Taina Kyrönlampi; Marja-Leena Böök; Hannele Karikoski (Journal of Early Childhood Education Research, 2020)
This study investigated obstacles to encounters with staff as experienced by parents in the context of institutional pre-primary education in Finland. The study contributes to education research by exploring parents’ perceptions and experiences of encounters with staff from the perspectives of Buber’s (1923/1987; 1947/2002) dialogic philosophy and Giorgi`s (1994) phenomenological psychology. The parent volunteers (n = 15) who participated in planning the local pre- primary education curriculum based on The National Core curriculum for Pre-primary Education 2014 (Finnish National Board of Education 2016) met three times during the 2015–2016 school year in a city in northern Finland. In the last meeting there were five parents, whose group discussion the results of this study are principally based. The parents expressed a desire for more openness and transparency regarding daily life events and practices in pre-primary schools. They also felt that power relations created barriers to cooperation in the sense that staff did not take account of parents’ perspectives on their children. The findings clarify how encounters between parents and staff crystallize in daily face-to-face discussions and suggest that dialogue between parents and staff requires time, a calm situation, a family-friendly approach, and the willingness of parents and staff to work together.